Efektivitas Penggunaan Google Scholar dalam Menunjang Proses Penulisan Skripsi Mahasiswa Perpustakaan dan Ilmu Informasi - Sofyah Aprilia, Siti; Marlini, Marlini (Scinary, 2025)
This study examines students' acceptance of Google Scholar as a medium for searching scientific literature using the Technology Acceptance Model (TAM) approach. This study is quantitative and involves students at Padang State University, specifically Library and Information Science students from the 2021 cohort who use Google Scholar in the process of writing their theses. Data were collected from 74 participants selected using the Slovin formula. The questionnaire was designed based on the Technology Acceptance Model (TAM) theory. The primary focus of the study was on two dimensions within TAM: Perceived Usefulness (perceived benefits) and Perceived Ease of Use (perceived ease of use). The research results indicate that the acceptance level of Google Scholar is very high, with an average usefulness score of 3.29 and an average ease of use score of 3.25, both falling into the “Very Good” category. The platform is considered most effective in helping students obtain academic information and facilitating literature searches. However, there are some aspects that still need improvement, such as its contribution to research productivity and the clarity of its interface. Overall, these findings indicate that Google Scholar has been able to meet students' expectations as a useful and easy-to-use tool. The balance between the two dimensions of TAM reflects the functional maturity of the platform in supporting academic research needs. This study also recommends institutional support through training in the use of Google Scholar and further research using a mixed-method approach to gain a deeper understanding.